ASPECTS REGARDING THE RECOVERY OF THE ANKLE SPRAIN BY MYOFASCIAL TECHNIQUES - Kristo XHARDO; Mariana CORDUN; Oana Maria BALTAG; Virgil TEODORESCU; George Sebastian IACOB (Cluj University Press, 2022)
Introduction: A sprained ankle is an injury that occurs when you roll, twist or turn your ankle in an awkward way. This can stretch or tear the tough bands of tissue (ligaments) that help hold your ankle bones together. The incidence of training injuries is almost constant for players between the ages of 13 and 19, with the majority of injuries ranging from 1 to 5 injuries per 1,000 hours of training, while younger players have lower incidences. The incidence of injuries during the match tends to increase with age, in all age groups, with an average incidence of about 15 to 20 injuries per 1,000 hours of play in players over 15 years of age. Objective: The aim of this study is to verify the efectiveness of an individualized kinetic program in association with myofascial techniques. Methods: The myofascial techniques used are IASTM (Ergon therapy), dry needling, cupping and kinesiotaping. In this study a 18 years old football player was included. The evaluation was performed by the Biodex (for the muscle strength) and lunge test (for the range of motion). Results: After a month o treatment, our patient improved his strength and range of motion. Conclusion: Studies have shown that these techniques of myofascial release provide a huge effectiveness on the flexibility of the muscles, having even much more efficacy than stretching. Using myofascial techniques, has a much quicker result on the recuperation of the ankle sprain offering a great efficacy on the total recuperation of the pacient. Article history: Received 2022 October 09; Revised 2022 October 20; Accepted 2022 October 21; Available online 2022 November 20; Available print 2022 December 20. REZUMAT. Aspecte privind recuperarea entorsei de gleznă prin tehnici miofasciale. Introducere: O entorsă a gleznei este o leziune care apare atunci când vă rostogoliți, răsuciți sau întoarceți glezna într-un mod neobișnuit. Acest lucru poate întinde sau rupe benzile dure de țesut (ligamente) care ajută la menținerea oaselor gleznei împreună. Incidența accidentărilor la antrenament este aproape constantă pentru jucătorii cu vârste cuprinse între 13 și 19 ani, majoritatea accidentărilor variind de la 1 la 5 accidentări la 1.000 de ore de antrenament, în timp ce la jucătorii mai tineri incidența este mai scăzută. Incidența accidentărilor în timpul meciului tinde să crească odată cu vârsta, la toate grupele de vârstă, cu o incidență medie de aproximativ 15 până la 20 de accidentări la 1.000 de ore de joc la jucătorii de peste 15 ani. Obiective: Scopul acestui studiu este de a verifica eficacitatea unui program kinetic individualizat în asociere cu tehnici miofasciale. Metode: Tehnicile miofasciale utilizate sunt IASTM (Ergon therapy), dry needling, cupping și kinesiotaping. În acest studiu a fost inclus un jucător de fotbal în vârstă de 18 ani. Evaluarea a fost efectuată cu Biodex (pentru forța musculară) și testul fandare (pentru amplitudinea de mișcare). Rezultate: După o lună de tratament, pacientul și-a îmbunătățit forța și amplitudine de mișcare. Concluzii: Studiile au arătat că aceste tehnici de eliberare miofascială oferă o eficiență uriașă asupra flexibilității mușchilor, având chiar mai multă eficacitate decât stretching-ul. Utilizarea tehnicilor miofasciale are un rezultat mult mai rapid la recuperarea entorsei gleznei oferind o mare eficacitate asupra recuperării totale a pacientului. Cuvinte cheie: terapie manuală, recuperare, entorsă de gleznă.